Production potential, sustainability and energetics of groundnut based intercropping systems in Upper Krishna Project command area of Karnataka: PRODUCTION POTENTIAL, SUSTAINABILITY AND ENERGETICS OF GROUNDNUT CROPPING SYSTEMS - S N HONNALI,; B M CHITTAPUR, (Journal of Oilseeds Research, 2014)
The field experiment conducted to evaluate the productivity and energetics of groundnut based intercropping systems during rabi/summer in UKP (Upper Krishna Project) command area of Karnataka revealed higher groundnut equivalent yield (GEY, 2.40 and 2.41 t/ha, respectively), monetary returns (Gross returns ` 84045 and ` 84180, net returns ` 64522 and ` 64220, and B:C ratio of 3.29 and 3.21, respectively) and energy output (12.61 x 106 and 12.82 x 106 K cal/ha, respectively) with groundnut + sesame in 4:2 and 5:1 row proportions followed by groundnut + maize in 4:2 row ratio (2.19 t/ha GEY, ` 76531 gross returns, ` 55981 net returns, 2.73 B:C ratio, and 16.15 x 106 K cal/ha energy output). Groundnut + sunflower was not advantageous over sole groundnut (2.01 and 1.99 t/ha yield equivalent, ` 68786 gross returns, ` 49058 net returns, 2.49 B:C ratio, and 11.14 x 106 K cal/ha energy yield). While, sole crops of maize, sunflower and sesame were poor in their productivity in comparison to groundnut. Thus, on-farm groundnut crop diversification through intercropping was advantageous during rabi/summer in UKP command area of Karnataka.